Creative writing and the new humanities - Dawson, Paul, 1972- (London ; New York : Routledge, 2005)
"In this new book, Paul Dawson demonstrates that the discipline of Creative Writing developed as a series of pedagogic responses to the long-standing 'crisis' in Literary Studies. He traces the emergence of Creative Writing alongside the New Criticism in American universities; examines the writing workshop in relation to theories of creativity and literary criticism; and analyses the evolution of Creative Writing pedagogy alongside and in response to the rise of 'Theory' in America, England, and Australia."--BOOK JACKET.
Introduction : building a garret in the ivory tower -- 1. From imagination to creativity -- 2. Disciplinary origins -- 3. Workshop poetics -- 4. Creative writing in Australia -- 5. Negotiating theory -- 6. What is a literary intellectual? -- Conclusion : towards a sociological poetics.
Includes bibliographical references (p. [218]-244) and index.
Keywords: English language -- Rhetoric -- Study and teaching; Creative writing (Higher education); Humanities -- Study and teaching